Macroeconomic impact of the Itaipú Treaty review for Paraguay - Che, Natasha (International Monetary Fund, 2021)
With the debt obligation of Itaipu Binational being completed paid off by 2023, the Annex C of the Treaty of Itaipu, which governs the operation and revenue distribution of the Itaipu Dam, is due for review and possible revisions. The implications for Paraguay's export revenues and fiscal position are potentially significant. The paper reviews the current energy distribution and sales arrangements of Itaipu and the potential implication of the Annex C revision for the future
10.5089/9781513573755.001
Keywords: Graue Literatur; Renewable Energy policy; Itaipú Binational; Natural Resource Management; Trade; Electric Utilities; Foreign Exchange; Informal Economy; Underground Econom; Energy; Natural Resources; Economics: General; Investments: Energy; Exports and Imports; Trade: General; Fiscal Policy; Alternative Energy Sources; Agricultural and Natural Resource Economics; Environmental and Ecological Economics: General; Economic & financial crises & disasters; Economics of specific sectors; Investment & securities; International economics; Environmental management; Macroeconomics; Electricity; Commodities; International trade; Fiscal stance; Renewable energy; Environment; Currency crises; Informal sector; Economics; Electric utilities; Exports; Fiscal policy; Renewable energy sources; Natural resources